1981
DOI: 10.1051/rnd:19810511
|View full text |Cite
|
Sign up to set email alerts
|

In vitro effect of a fish gonadotropin on aromatase and 17 β-hydroxysteroid dehydrogenase activities in the ovary of the rainbow trout (Salmo gairdneri Rich.)

Abstract: Summary. Aromatase activity has been studied in the rainbow trout ovary in a perifusion system. During early vitellogenesis, as in other stages of the annual cycle, the ovaries were capable of aromatizing androstenedione and testosterone. Aromatase activity increased from the postovulatory stages to exogenous vitellogenesis.When highly purified salmon glycoprotein maturational gonadotropin was added to the medium (50 ng/ml), the androstenedione/testosterone ratio was reduced by half. This indicates a stimulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

1988
1988
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…A tritiated water release assay was used to measure aromatase activity, as previously described (Fostier, 1995). Androstenedione was chosen as a precursor due to its higher metabolization efficiency by trout ovarian aromatase, in comparison to testosterone (Sire and Depeche, 1981). One hundred rainbow trout follicles, 100 oocyte extracts, and 100 corresponding follicular layers were homogenized on ice in 8 ml phosphate buffer pH 7.55 using an Ultra‐Turrax.…”
Section: Methodsmentioning
confidence: 99%
“…A tritiated water release assay was used to measure aromatase activity, as previously described (Fostier, 1995). Androstenedione was chosen as a precursor due to its higher metabolization efficiency by trout ovarian aromatase, in comparison to testosterone (Sire and Depeche, 1981). One hundred rainbow trout follicles, 100 oocyte extracts, and 100 corresponding follicular layers were homogenized on ice in 8 ml phosphate buffer pH 7.55 using an Ultra‐Turrax.…”
Section: Methodsmentioning
confidence: 99%
“…Working with amago salmon Kagawa et al (1982) and Young et al ( , 1983 have suggested that a twocell process of oestradiol biosynthesis may operate in which androgens synthesized by the theca are transformed to oestrogens by aromatase action in the granulosa. Sire and Depeche (1981) have also shown that gonadotrophin inhibited aromatase activity in rainbow trout ovaries incubated in vitro. By contrast, the GTH stimulated granulosa preparation produced a small amount of oestradiol (max 4 ng/ml, Fig.…”
Section: Discussionmentioning
confidence: 84%
“…Indeed, Jalabert (1975) has shown that oestradiol exerts some inhibitory influence on the gonadotrophin induced maturation of rainbow trout follicles in vitro. In teleosts as in other vertebrate classes C19 androgenic steroids, serving as substrated for aromatase enzymes are the precursors of oestrogens (Sire and Depeche 1981;Fostier et al 1983). Interest in its biosynthesis during oocyte final maturation then stems principally from the better understanding which may accrue of the rapidly changing pattern of steroid hormone synthesis which occurs at this time.…”
Section: Discussionmentioning
confidence: 99%
“…As their expression in the differentiating ovary is high at a time when testosterone and 17β‐estradiol metabolism is active (Petkam et al, ), Shbgb could serve to protect both from being degraded. Shbgb could also restrict the availability of testosterone as a substrate for aromatase, leaving the alternative substrate, androstenedione (Sire and Dépêche, ), more available for conversion by the enzyme. Other Shbgb functions involving the mechanism of action of sex steroids during the ovarian differentiation could exist (Caldwell and Jirikowski, ), and need to be further investigated.…”
Section: Discussionmentioning
confidence: 99%